Case report: Anti-N-methyl-D-aspartate receptor antibody-associated autoimmunity triggered by primary central nervous system B-cell lymphoma - Yokota, Yuki; Hara, Makoto; Oshita, Natsuki; Mizoguchi, Tomotaka; Nishimaki, Haruna; Hao, Hiroyuki; Nakajima, Hideto (Frontiers in Neurology, 2023)
Background We herein detail our experience with a unique patient with a primary central nervous system (PCNS) B-cell lymphoma concomitant with anti-N-methyl-d-aspartate receptor (NMDAR) antibodies that satisfied the criteria of “probable anti-NMDAR encephalitis (ProNMDARE)” based on the Graus criteria 2016. Case presentation A 73-year-old Japanese woman presented with acute pyrexia, agitation, and disturbance of consciousness. She gradually developed a reduction in speech frequency and truncal dystonia causing abnormal posture. Brain magnetic resonance imaging (MRI) demonstrated high-intensity lesions in the bilateral frontal lobes, and her cerebrospinal fluid revealed mild pleocytosis. She was diagnosed with acute encephalitis and treated with acyclovir and intravenous dexamethasone; however, no improvement was observed. She was transferred to our hospital 6 weeks after the onset of her symptoms, and anti-NMDAR antibodies were identified in her cerebrospinal fluid through indirect immunolabeling with rat brain frozen sections and cell-based assays with NR1/NR2 transfected HEK cells. Follow-up MRI showed enlargement of the lesions in the right frontal lobe with gadolinium enhancement, suggesting a brain tumor. Stereotactic surgery was implemented, with subsequent pathological examination revealing that the tumor was consistent with diffuse large B-cell lymphoma (DLBCL) without evidence of systemic satellite lesions. Stereotactic irradiative therapies were then added to her treatment regimen, which partly improved her neurological symptoms with only mild cognitive dysfunction still remaining. A decrease in anti-NMDAR antibody titer was also confirmed after immunotherapy and tumor removal. Conclusions We herein report our experience with a novel case of PCNS-DLBCL masquerading as anti-NMDAR encephalitis that satisfied the diagnostic criteria of “proNMDARE.” Treatment, including tumor removal, ameliorated disease severity and antibody titers of the patient. Our findings suggest that anti-NMDAR antibody-associated autoimmunity can be triggered by PCNS B-cell tumors, although primary brain tumors need to be excluded before establishing a diagnosis of autoimmune encephalitis.